Long-Term Outcome of Patients Undergoing Minimally Invasive Direct Coronary Artery Bypass Surgery: A Single-Center Experience. Issue 1 (January 2018) - Farid, Shakil; Ali, Jason M.; Stohlner, Victoria; Alam, Ruhina; Schofield, Peter; Nashef, Samer; De Silva, Ravi
Objective: The primary objective was to investigate the long-term survival of patients who underwent single-vessel coronary revascularization with minimally invasive direct coronary artery bypass surgery with or without hybrid revascularization. The secondary outcome measures were repeat revascularization either by coronary artery bypass grafting or by percutaneous coronary intervention and the incidence of myocardial infarction or recurrent angina. Methods: This is a retrospective study of prospectively collected data of patients who underwent minimally invasive direct coronary artery bypass procedure in our center between January 2001 and December 2015. Procedures were performed either through small left anterolateral thoracotomy or lower midline sternotomy. Results: A total of 182 patients were identified: 100 underwent minimally invasive direct coronary artery bypass to the left anterior descending artery and 82 underwent hybrid revascularization (percutaneous coronary intervention to coronary arteries other than the left anterior descending artery along with minimally invasive direct coronary artery bypass to the left anterior descending artery). The mean ± SD age was 62 ± 10.1 years. Preoperatively 82% were male, and 72.5% patients had good left ventricular function. The median follow-up period was 10.9 years. There was no inhospital or 30-day mortality. The 10-year actuarial survival was 84.8%. Freedom from repeat revascularization was 98.9% at 1 year and 89.9% at 10 years. At follow-up, freedom from myocardial infarction was 96.7% whereas freedom from angina was 92.9%. Conclusions: Within the limitations imposed by retrospective analyses, our study demonstrates excellent long-term outcome in patients undergoing minimally invasive direct coronary artery bypass with or without hybrid revascularization. For isolated left anterior descending artery disease minimally invasive direct coronary artery bypass should be considered, whereas hybrid revascularization (percutaneous coronary intervention and minimally invasive direct coronary artery bypass) should be considered for multivessel disease.